Human T cells expressing BEND3 on their surface represent a novel subpopulation that preferentially produces IL‐6 and IL‐8. Issue 1 (19th February 2014) - Shiheido, Hirokazu; Kitagori, Koji; Sasaki, Chiyomi; Kobayashi, Shio; Aoyama, Takane; Urata, Kozue; Oku, Takuma; Hirayama, Yoshitaka; Yoshitomi, Hiroyuki; Hikida, Masaki; Yoshifuji, Hajime; Mimori, Tsuneyo; et al.
Abstract BEN domain‐containing protein 3 (BEND3) has no transmembrane region, is localized in the cytoplasm, and is involved in chromatin function and transcription. We here identified a novel subpopulation of human T cells that expressed BEND3 on their cell surface (BEND3+ T cells). BEND3+ T cells consisted of approximately 3% of T cells in the peripheral blood, were present in both CD4+ and CD8+ T cells, and were also observed in cord blood. The stimulation of BEND3+ T cells through the TCR/CD3 complex led to the production of various kinds of cytokines; however, the levels of IL‐6 and IL‐8 produced by BEND3+ T cells were higher than those by BEND3− T cells. The proportion of BEND3+ T cells was also increased in some patients with inflammatory diseases. Taken together, these results indicate that BEND3+ T cells are a new subpopulation of T cells in terms of their cytokine profile. Further analyses on BEND3+ T cells may be of importance and useful in understanding human T cell immunology.